Advanced mechanics in robotic systems - Nava Rodríguez, Nestor Eduardo; SpringerLink (Online service). (London Springer London, 2011)
Humans have always been fascinated with the concept of artificial life and the construction of machines that look and behave like people. As the field of robotics evolves, it demands continuous development of successful systems with high-performance characteristics for practical applications. Advanced Mechanics in Robotic Systems illustrates original and ambitious mechanical designs and techniques for developing new robot prototypes with successful mechanical operational skills. Case studies are focused on projects in mechatronics that have high growth expectations: humanoid robots, robotics hands, mobile robots, parallel manipulators, and human-centred robots. A good control strategy requires good mechanical design, so a chapter has also been devoted to the description of suitable methods for control architecture design. Readers of Advanced Mechanics in Robotic Systems will discover novel designs for relevant applications in robotic fields, that will be of particular interest to academic and industry-based researchers.
Humanoid Robots -- Robotic Hands -- Mobile Robots -- Parallel Manipulators -- Human Centred Mechatronics -- Mechanical Design Thinking of Control Architecture.
Electronic reproduction.
Keywords: Robotics; Mechanics; Electronic books